Propuesta de protocolo de atención odontológica dirigida a pacientes de oncología pediátrica - De la Cadena Vivanco, Noelia Elizabeth (2019)
This is a cross-section descriptive type study which main objective is to propose a dental care protocol focused on pediatric oncology patients, through the analysis of theoretical bases, references to the identification of frequent oral pathologies, manifestations and therapeutics; As well as recommendations obtained by professionals through the participants considered for the thesis project. Methodology: A total of 32 health professionals were taken into consideration for the research project: general dentists (n = 11), pediatric dentists (n = 8), pediatricians (n = 11) and oncologists (n = 2); Concerning the development of field study, the application of surveys was carried out in line with scientific bases established for each training area of the professionals involved. The data collected from the surveys were imported into the SPSS program version 24.0.0.0, and later statistics were analyzed in a descriptive way on Microsoft Excel. Results: it was possible to verify that the vast of majority of the participants use a protocol that is easy to use and understand for both professionals and families. A printed and digital version is available (53%) with information simplified in regards to education, prevention and treatment; therefore, dentists expressed that as a result of antineoplastic treatment the most frequent oral symptoms observed during medical consultation were: candidiasis (17%), mucositis (14%), xerostomia (13%) and herpetic lesions (12 %). Key words: pediatric dentistry, pediatrics, protocols, cancer, therapeutics.